The Role of Emotional Intelligence in Mitigating Employee Turnover: A Psychological Approach - Nugraha, Risman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research investigates the pivotal role of Emotional Intelligence (EI) in mitigating employee turnover from a psychological perspective. Emotional Intelligence—encompassing self-awareness, empathy, and stress management—is identified as a crucial factor in enhancing job satisfaction and organizational commitment, thus influencing employee retention. Employing a library research methodology, the study reviews existing literature on EI's impact on reducing turnover and highlights how high EI levels contribute to lower turnover rates by improving job satisfaction and fostering a stronger commitment to the organization. The study finds that employees with elevated EI are adept at managing workplace stress, fostering positive relationships, and aligning with organizational values. This alignment enhances their job satisfaction and commitment, leading to reduced turnover rates. The findings have practical implications for organizations, suggesting that integrating EI assessments into recruitment processes, developing EI training programs, and creating supportive work environments can significantly improve employee retention. Prioritizing EI development helps in building a more resilient and engaged workforce, thereby contributing to organizational stability and performance.